Enhancing Trust and Purchase Intention through Optimized Seller Pages and Experience Features: Insights from Indonesia’s E-Marketplaces - Ayu Rinestri, Titis; Nur Kolilah, Fatma; Lusdianingrum, Sitista Silvi; Syaifulloh, Naf’an Kharis; Kusuma Negara, Wana Pramudyawardana (Profesional Muda Cendekia Publishing, 2025)
Research Aims: this ponder explores the impact of vender page and customer encounter highlights on shopper believe and buy deliberate inside the quickly extending Indonesian e-marketplace . Grounded in the Stimulus-Organism-Response (S-O-R) framework, the research examines how these features act as stimuli, shaping consumer trust (organism) and subsequently influencing purchase intention (response). Design/methodology/approach: Data from 323 Indonesian e-marketplace users (aged 18-45), gathered via an online survey with purposive sampling, were analyzed using SEM-PLS. Research Findings: This study found a positive relationship between seller page features and consumer trust, consumer experience features and consumer trust, and consumer trust and purchase intention. Seller page features demonstrated the strongest influence on trust, likely due to their role in conveying seller credibility. Theoretical Contribution/Originality: The findings contribute theoretically by extending the S-O-R framework to the unique context of emerging markets, where trust remains important to e-commerce. Practically, the study provides actionable insights for e-marketplace operators and sellers in Indonesia, offering guidance on optimizing e-marketplace adoption to foster trust and drive purchase intention. Keywords: Seller Pages, Experience Features, Trust in Seller, Purchase Intention.